Influence of neuropathological diagnosis on psychooncological distress in neurooncological patients - a retrospective cross-sectional analysis - Staub-Bartelt, Franziska; Obermayr, Sarah; Sabel, Michael; Rapp, Marion (Frontiers in Oncology, 2024)
BackgroundGliomas, the most common primary brain tumours, are classified based on histology and molecular genetics. Glioblastomas (GBM) are highly aggressive and are graded as WHO grade 4, while astrocytoma and oligodendrogliomas fall under WHO grades 2-3 (4). Gliomas affect 6 per 100,000 people, with a higher incidence in men. GBM has the poorest prognosis, whereas grade 2 astrocytoma and oligodendrogliomas show better outcomes. Quality of life (QoL) is now a crucial therapeutic goal alongside survival. Despite the impact of gliomas on QoL, especially given their incurability and progressive neurological deficits, research specifically comparing QoL and psycho-oncological stress in GBM versus grade 2 gliomas (glioma_2) remains limited. This study aims to fill that gap using validated measurement methods.MethodsThis retrospective, single-centre study investigated differences in QoL among neuro-oncological patients using the Karnofsky Performance Score (KPS), Distress Thermometer (DT), Hospital Anxiety and Depression Scale (HADS), and EORTC-QLQ-C30-BN20. Data were collected before chemotherapy or radiotherapy to avoid therapy impact on QoL. Out of 2258 patients screened until June 30, 2022, 639 had glioblastoma or WHO grade 2 gliomas, with 223 meeting inclusion criteria for analysis.ResultsThe study included 161 GBM and 62 Glioma_2 patients, with 64% of all patients being male. The mean age was 58.11 years (SD ± 16.186). The DT did not show significant differences between GBM and glioma_2 glioma patients (median GBM:6 vs. 5 in glioma_2, p=0.480). However, the HADS-D indicates that GBM patients experience significantly more depression (median GBM 4.5 vs. 4 in glioma_2, p=0.033), though anxiety levels are similar in both groups (median GBM. 6 vs. 6 in glioma_2, p=0.867). The KPS (median GBM 70 vs. 90 in glioma_2, p<0.001) and specific aspects of the EORTC-QLQ-C30-BN20 questionnaire demonstrate that GBM patients have notably greater physical impairments than glioma_2 patients at diagnosis. Overall, GBM patients report worse quality of life compared to glioma_2 patients (median GBM 50 vs. 67 in glioma_2, p<0.001).ConclusionThis study showed that distress is present in glioma patients regardless of their histopathological grading, even though GBM patients show higher depression levels and more physical limitations. Targeted anxiety management and early depression screening are essential for all glioma patients. Early QoL screening and making QoL a therapeutic goal benefits patient care and society.